Autocatalytic DNAzyme assembly for amplified intracellular imaging. Issue 77 (17th September 2020) - Gong, Keke; Wu, Qiong; Wang, Hong; He, Shizhen; Shang, Jinhua; Wang, Fuan
Abstract : An autonomously catalytic assembly of an HCR-DNAzyme circuit was facilely constructed for reliable intracellular miR-21 imaging. Abstract : The autocatalytic HCR-DNAzyme platform was constructed as a versatile amplification platform for intracellular microRNA imaging by integrating hybridization chain reaction (HCR) circuit with DNAzyme biocatalysis. The HCR-assembled multifunctional DNAzyme nanowires produce new HCR triggers and numerous transducer DNAzyme amplifier, and thus shows great promise in earlier cancer diagnosis.